Factors related to the length of stay for major depressive disorder patients in China: A real-world retrospective study - Cheng, Peng; Wang, Lirong; Xu, Lizhi; Zhou, Ying; Zhao, Guangju; Zhang, Li; Li, Weihui (Frontiers in Public Health, 2022)
Background: As numerous patients with depression have to be hospitalized due to various reasons, the demand far exceeds the limited bed count in the psychiatry department. Controlling the length of stay (LOS) of the patient is gradually being considered as an effective method to alleviate this problem. Given the lack of statistical evidence of the LOS of depression patients in China and the strain on limited psychiatric resources, the purpose of our study was to investigate the LOS of patients with depression among in-patient samples and to analyze related factors of the LOS in China by building a regression model. Method: The data was exported from the electronic medical record system. A total of 3 categories of independent variables were enrolled in our study, including demographic, clinical, and biochemical. Univariate analysis and binominal regression analysis were comprehensively applied to find the factors related to the LOS among depression samples. The discrimination accuracy of the model was evaluated by receiver operating characteristic (ROC) analysis. ROC analysis indicated that the discrimination accuracy of our model was acceptable (AUC=0.790, 95CI=0.714-0.865, P<0.001). Result: A total of 254 patients were finally brought into analysis after filtering. Regression analysis indicated that abnormal LDL was the only risk factor of long LOS (OR=3.352, 95CI=1.087-10.337, P=0.035) among all kinds of variables. Notably, in the statistically irrelevant factors of the LOS, the category of anti-depressant drugs (serotonin-norepinephrine reuptake inhibitor (SNRI) or selective serotonin reuptake inhibitor (SSRI)) chosen by depression patients was not statistically associated with the LOS, which was againstour initial hypothesis that the LOS of depression patients treated with SNRI would vary from that of patients treated with SSRI. Conclusion: Up to our knowledge, our research is the first study to show the potential factors related to the LOS from various domains, especially biochemical indexes, and the effect of drugs, among the clinical depression patients in China. Our results could provide a theoretical reference for efficient psychiatry hospitalization management and prioritization of allocating medical resources. Future studies are needed for updating independent variables which are potentially related to the LOS and verifying existing results in a larger sample.